The Influence of Information Quality and Public Relations Services at SMAN 7 Depok Using Whatsapp Group on Student Parent Satisfaction - Mulyadi, Ahmad; Prihantoro, Edy (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of information quality and public relations (PR) service quality at SMAN 7 Depok, delivered via WhatsApp Group, on student parent satisfaction. Along with technological developments, digital communication platforms like WhatsApp have become essential for schools to deliver information and services to parents. In this context, accurate, relevant, and timely information, along with responsive and professional service, is crucial for enhancing parental satisfaction with school services. This research uses a quantitative approach with a survey method. The sample for this study comprises parents of 10th-grade students at SMAN 7 Depok who actively use WhatsApp Group as a communication medium with the school. Data collection was conducted through online questionnaires, and data analysis utilized regression testing to examine the relationship between the variables of information quality, service quality, and parent satisfaction. The results show that the quality of information and services provided through WhatsApp Group significantly influences student parent satisfaction. High-quality information, such as timeliness and accuracy, along with responsive service from the school, positively impacts the level of parental satisfaction. These findings provide valuable insights for schools in managing communication and services through digital media and encourage improvements in PR strategies to maintain strong relationships with parents.